Burden of Skin and Subcutaneous Diseases in Indonesia 1990 to 2019 - Faida Ufaira Prameswari; Farizal Rizky Muharram; Trisniartami Setyaningrum; Cita Rosita Sigit Prakoeswa (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)